Микроволновые детекторы ионизирующих излучений - Сорока, А. С.; Бородин, Б. Г.; Галат, А. Б. (ХНУРЭ, 2010)
Создание надежных высокочувствительных дозиметров ионизирующих излучений и приборов радиационного мониторинга – важная задача в условиях активно развивающейся атомной энергетики и других отраслей науки и техники. В настоящее время наибольшее распространение получили твердотельные полупроводниковые приборы контроля радиационных источников. The development of contactless semiconductor microwave-biased detectors (microwave SMD) for registration of ionizing radiations will allow to overcome a number of technological res-trictions inherent traditional SMD, to simplify a design, to raise reliability and efficiency of the detector. The price of such solution is some complication of signal extraction and processing of a primary signal at high frequencies. The purpose of work - to offer an adequate radiophysical methods and means for radi-ometry of ionizing particles. In the work the criteria of choice of a frequency range and development of designs of effective mic-rowave resonant sensor for detecting ionizing radiations are proved on the basis of an analysis of the factor of efficiency.
Keywords: высокочувствительный дозиметр; ионизирующее излучение; твердотельные полупроводниковые приборы; радиационные полупроводниковые детекторы